New Records of Lichen for the Mycota of Assam State, Eastern Himalaya - Daimari, Rebecca; Nayaka, Sanjeeva; Upreti, Dalip K.; Hoque, Raza R. (Indian Forester, 2017)
In the ongoing studies on lichens of Assam state, samples collected from Sonitpur district resulted in 25 species hitherto not known from the state. These new records included 16 pyrenocarpous lichens with dominance of members from family Pyrenulaceae (11 spp.) followed by Physciaceae with five species among the newly encountered lichens.